Lateral plantar nerve injury following steroid injection for plantar fasciitis. Issue 12 (23rd November 2005) - Snow, D M; Reading, J; Dalal, R
Abstract : A 41 year old man presented with pain and numbness affecting the lateral aspect of his foot after a steroid injection for plantar fasciitis. Examination confirmed numbness and motor impairment of the lateral plantar nerve. The findings were confirmed by electromyographic studies. The anatomy of the lateral plantar nerve and correct technique for injection to treat plantar fasciitis are discussed.